Работы Боспорской охранно-археологической экспедиции в 2008 г. - Зинько, В.Н.; Зинько, А.В.; Твардецкий, А. (Археологічні дослідження в Україні, 2009)
In 2008, the Bosporan protective archaeology expedition continued the excavations of Tyritake. At the area XXVI of 1025 м2, structures of the earliest stages of the second—third quarters of the 6th c. BC and the last quarter of the 6th c. — the first quarter of the 5th c. BC were studied. At the area XXVII, near the Western wall of the city, the Polish group researched the remains of the Late Ancient structures on the area of 150 м2. At the area XXVIII of 200 м2, the remains of the Northern fortification and the detached two buildings of the 5th through the 6th c. AD were excavated over 20 m long.